Unconditionally stable ADI-FDTD formulations of the APTAL for frequency-dependent media - Ramadan, O (IEEE-Inst Electrical Electronics Engineers Inc, 2004)
Unconditional stable formulations of the anisotropic perfectly matched layer (APML) are presented for truncating frequency-dependent media. The formulations are based on the auxiliary differential equation and the alternating direction implicit finite-difference time-domain (ADI-FDTD) methods. Numerical examples carried out in one and two dimensions show that the proposed formulations remain unconditionally stable with inclusion of material dispersion into ADI-FDTD implementation of APML.
Keywords: alternating direction implicit (ADI); anisotropic perfectly matched layer (APML); auxiliary differential equation; finite difference time-domain (FDTD); frequency-dependent media